The dynamic landscape of cortical synaptic inhibition - Burman, RJ (2022)
Fast synaptic inhibition shapes cellular responses and network activity in the mammalian cortex. This inhibition is principally mediated by the activation of ionotropic GABA-A receptors (GABAARs), which are permeable to chloride (Cl-). For this reason, GABAAR function is intrinsically linked to processes that regulate the distribution of Cl- on either side of the neuronal membrane. Despite their fundamental role, the manner by which synaptic GABAARs function in the intact cortex has remained unknown. In this thesis, I explore how GABAAR-mediated synaptic signalling operates across different brain states and neuronal cell types in the mammalian cortex. To achieve this aim, I establish in vivo gramicidin perforated patch-clamp recordings, which enable me to study GABAAR function in the living rodent cortex, whilst preserving the integrity of the transmembrane Cl- gradient. By combining this method with pharmacological manipulations, I confirm that Cl- co-transporter proteins play a key role in establishing the equilibrium potential for GABAARs (EGABAAR) in vivo. I then use in vivo gramicidin perforated patch-clamp recording to reveal that GABAAR synaptic signalling is predominately shunting in the awake cortex. his results from relatively depolarised EGABAAR values, which arise due to the high levels of local network activity in the awake state. I further show that the animal’s sleep-wake history also contributes in setting EGABAAR in the awake cortex, consistent with evidence that sleep-wake history can modulate the activity of Cl- co-transporter proteins. To extend my studies into different neuronal cell types, I then establish a novel optogenetic method for probing intracellular Cl- regulation. By using a light-activated Cl- channel, I reveal differences in both the steady-state Cl- levels and Cl- extrusion capacities of two genetically-defined neuronal populations in the cortex, pyramidal neurons and parvalbumin-expressing interneurons. Taken together, the findings of this thesis support the idea that the ‘landscape’ within which GABAARs function is highly dynamic, depending on both the cortical state and neuronal cell type. This has important implications for how GABAAR function should be conceptualised within the cortex.